God, service, love the three pillars of GSL Food Enterprises - Shuck, Vlademir A. (Davao City School of Management, University of the Philippines Mindanao, 2007)
This study proposes a strategic plan for GSL Food Enterprise (GSL). Specifically, it aims to: (1) identify the company's strengths and weaknesses; (2) examine the external dimensions of the industry through opportunity and threat identification; (3) formulate an array of strategic options: (4) recommend the best strategic choice; (5) generate a program for the implementation of the strategic choice; and (6) conduct a monitoring and evaluation mechanism that will enable management to tract the progress of the plan's implementation. The proponent mainly utilized primary data in the analysis of this study from GSL archives. Actual financial figures used in the financial analysis came from the data bank of the accounting department of the company. Both the internal and external factors affecting the company were carefully analyzed in order to come up with the strategic options which will set the direction of the company for the next five years (2008-2012). The results of the study show that GSL demonstrates a strong internal position and possesses the ability to effectively respond to its external environment. Strategic options were formulated based on the results of the environmental analyses and the subsequent objective setting exercise. Three strategic options were selected from among the array of choices employing the Quantitative Strategic Planning Matrix (QSPM). These garnered the highest QSPM scores: Market Development, Product Leadership, and Product Development. Considering the existing local demand for banana chips and the size of the Middle East Market, it is very logical to exploit both new market opportunities. Product quality, as one of the major focus of the company, can be highlighted more through employing product leadership strategy. This is expected to bring higher profit to the company due to the distinctive characteristic of the high end market in choosing high quality products even at a premium price. Continuous product development is the long term strategy of the company. Moreover, the competitiveness of the product is maintained by keeping abreast with the newest trends in the industry, Thus, the remaining challenge in the part of the management will be proper implementation, monitoring and evaluation of the outcomes of the chosen strategies.
Thesis, Graduate (Master in Management)--University of the Philippines Mindanao, 2007
Keywords: Strategic plan